ESTOQUES DE CARBONO ORGÂNICO NO SOLO EM ÁREA DE PASTAGEM SUBMETIDA AO MÉTODO DE PASTEJO CONTÍNUO - PAULINO, Leonardo Albino; IMBRIANI, João Marcos Morais; AGUIAR, Franciele Kelle Oliveira Moura; LIMA, Isabela Machado de Oliveira; BARBOSA, Giselle Feliciani (ANAIS DO ENIC, 2020)
-